Inovasi Budidaya Jamur Tiram Sebagai Penghasilan Tambahan Di Masa Pandemi - Ratna Marta Dhewi; Rakhmini Juwita; Suhartono Suhartono; Veronica Kristiani (Jurnal Abdi Masyarakat (JAM), 2023)
During the Covid-19 pandemic, residents of Talun Village in Rangkasbitung saw the benefits of oyster mushroom farming as an alternative source of income. The Community Service Team is primarily concerned with mapping the problem and developing a solution plan to raise the quantity, quality, and economic worth of oyster mushroom production. To attain the aims, participatory learning, field practice, monitoring, and evaluation are used. To ensure the sustainability of the cultivation, a total of 20 youth members of the youth organization were participating. The following innovation outcomes were achieved: 1) improving mushroom quality by increasing baglog nutrition with the addition of corn groats; 2) the introduction and use of mixing machines for mixing materials; 3) the introduction and use of autoclaves and boiler machines; 4) the use of manual log molds and folding plastic; and 5) mushroom harvesting technique innovation